Waris Beda Agama Dalam Perspektif Hukum Islam: Studi Komparasi Pemikiran Wahbah Az-Zuhali dan Yusuf Al-Qaradawi - Musadat, Ahmad (Al-Mazaahib: Jurnal Perbandingan Hukum, 2016)
Although the legal provisions on inheritance from different religions in Islam have actually been rolled out for a long time. There is no clear spot regarding the inheritance of different religions at this time. Evidence that there are still differences of opinion regarding the issue of inheritance from different religions here, namely between Wahbah az-Zuhaili and Yusuf al-Qaradawi. Wahbah az-Zuhaili prohibits inheritance from different religions, but Yusuf al-Qaradawi with his minority fiqh rejects the absolute prohibition of inheritance, but only prohibits harbi infidels. The type of this research is Library Research. This research is descriptive, analytic, comparative The approach used by the authors is the uṣul al-fiqh approach by using muṭlaq and muqayyad theories. The approaches and theories above are to find out the differences in thoughts and backgrounds that cause these two figures to be different. In this difference, Wahbah az-Zuhaili absolutely rejects the inheritance of different religions because of his understanding of the hadith of the Prophet. Because Wahbah az-Zuhaili views this hadith of the prophet as absolute, so the meaning of the word infidel in the hadith is interpreted comprehensively for all infidels without exception. absolute. Because according to him the hadith of the Prophet still has a broad meaning. The theory which is considered as a muqayyad theory of hadith interpretation here causes the word infidel in that hadith to be interpreted as the takwil of followers of the Hanafi school of thought. The interpretation here specifies the word infidel from the word infidel to infidel harbi only. Yusuf al-Qaradawi's theory is relevant in Indonesia because Indonesia itself recognizes religions other than Islam itself.